Knowledge Dissemination of Intimate Partner Violence Intervention Studies Measured Using Alternative Metrics: Results From a Scoping Review. Issue 9 (May 2019) - Madden, Kim; Evaniew, Nathan; Scott, Taryn; Domazetoska, Elena; Dosanjh, Pritnek; Li, Chuan Silvia; Thabane, Lehana; Bhandari, Mohit; Sprague, Sheila
Alternative metrics measure the number of online mentions that an academic paper receives, including mentions in social media and online news outlets. It is important to monitor and measure dispersion of intimate partner violence (IPV) victim intervention research so that we can improve our knowledge translation and exchange (KTE) processes improving utilization of study findings. The objective of this study is to describe the dissemination of published IPV victim intervention studies and to explore which study characteristics are associated with a greater number of alternative metric mentions and conventional citations. As part of a larger scoping review, we conducted a literature search to identify IPV intervention studies. Outcomes included znumber of alternative metric mentions and conventional citations. Fifty-nine studies were included in this study. The median number of alternative metric mentions was six, and the median number of conventional citations was two. Forty-one percent of the studies (24/59) had no alternative metric mentions, and 27% (16/59) had no conventional citations. Longer time since publication was significantly associated with a greater number of mentions and citations, as were systematic reviews and randomized controlled trial designs. The majority of IPV studies receive little to no online attention or citations in academic journals, indicating a need for the field to focus on implementing strong knowledge dissemination plans. The papers receiving the most alternative metric mentions and conventional citations were also the more rigorous study designs, indicating a need to focus on study quality. We recommend using alternative metrics in conjunction with conventional metrics to evaluate the full dissemination of IPV research.